Flavonoid Oligoglycosides from Ophioglossum vulgatum L. Having Wound Healing Properties - Clericuzio, Marco; Tinello, Stefano; Burlando, Bruno; Ranzato, Elia; Martinotti, Simona; Cornara, Laura; La Rocca, Arianna (Planta Medica, 2012)
Two new glycosylated and acylated flavonols, viz. quercetin-3-O-[(6-caffeoyl)-β-glucopyranosyl (1 → 3) α-rhamnopyranoside]-7-O-α-rhamnopyranoside (2), and kaempferol-3-O-[(6-caffeoyl)-β-glucopyranosyl (1 → 3) α-rhamnopyranoside]-7-O-α-rhamnopyranoside (3), together with the known quercetin-3-O-methyl ether (1), were isolated from the aerial parts of the fern Ophioglossum vulgatum L. Their structures were established by means of 1D and 2D NMR spectra, as well as ESI-MS and ESI-HRMS spectra. Compounds 1–3 were all found to be active in scratch-wound healing assays on keratinocytes, with 3 being the most active one and showing maximum activity at 20 µM.
Keywords: Ophioglossum vulgatum L.; Ophioglossaceae; quercetin acyl-glycosides; kaempferol acyl-glycosides; scratch-wound healing; keratinocytes